The Effects of a Maneevej Exercise Program Combined with Music on Depression in Older Adults After the COVID-19 pandemic - Aiamanan, Maneerat; Nirotnun, Urai; Magteppong, Wararat (Journal of Nursing and Public Health Research, 2025)
This quasi-experimental study aimed to examine the effect of a Maneevej exercise program combined with music on depression in older adults after the COVID-19 pandemic. The participants comprised 40 older adults who had experienced the COVID-19 pandemic and exhibited mild to moderate levels of depression. They were equally divided into an experimental group (n = 20) and a control group (n = 20). The experimental group participated in the Maneevej exercise program combined with music, following the program manual, twice daily for eight consecutive weeks. The control group received routine care according to the standard practices of healthcare facilities. The research instruments consisted of: 1) the Maneevej exercise program combined with music, 2) the Thai Geriatric Depression Scale, and 3) a personal data questionnaire. General data were analyzed using descriptive statistics. The differences in mean depression scores in the experimental group before and after the program were compared using paired t-test, and the differences between the experimental and control groups after the program were compared using independent t-test. The results showed that the mean depression scores in the experimental group after the intervention decreased significantly compared to the baseline (p-value < 0.001). However, there was no statistically significant difference in the post-intervention mean depression scores between the experimental and control groups (p-value > 0.05). Therefore, healthcare professionals can implement this program to promote older adults’ mental health and help prevent depression in the community following the COVID 19 pandemic.